Iron-bearing phases affecting the colour of upper Neogene clayey sediments from Dymaczewo Stare, west-central Poland - Klęsk, Jakub; Błachowski, Artur; Diduszko, Ryszard; Kruszewski, Łukasz; Widera, Marek (Geologos, 2022)
The present paper investigates the colour dependence of mineral compositions in clay-rich sedimentary strata, mainly clayey silts, the emphasis being on iron-bearing minerals (rather than clay minerals) by using powder X-ray diffraction (PXRD) and 57Fe Mössbauer spectroscopy (57Fe-MS). The PXRD-based phase analysis has demonstrated the variable compositions of samples, consisting of, inter alia, quartz, calcite or gypsum, and admixtures of potassium feldspars and plagioclase. Hematite + goethite (sample D1, dark red), goethite (sample D2, pinkish brown), poorly crystalline goethite (sample D3, orange) and jarosite (sample D4, yellow) have been distinguished. A very low jarosite content was detected in sample D5 (light grey); this did not affect its colour. The potential yellow/brown shades in sample D6 (dark grey), coming from trace amounts of jarosite, are masked by macroscopically visible organic matter. In the case of the two last-named samples (D5 and D6), with trace amounts of Fe-bearing minerals, it is most likely that the organic matter was effective in influencing the light and dark grey colour of the sediment, respectively.